2002
DOI: 10.1002/app.10393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preparation method on the capture and release of biologically active molecules in chitosan gel beads

Abstract: Model bioactive compounds with different molecular and functional characteristics were entrapped in gel beads prepared by polyelectrolyte complexation of chitosan and pentasodium tripolyphosphate (TPP). Three compounds of interest to the food and biomedical industries were tested: (1) lysine, (2) bovine serum albumin (BSA), and (3) ␤-galactosidase. Effects of the compound concentration in the initial chitosan solution, pH of the curing solution, and length of the curing phase on the capture efficiency were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Good capture efficiencies were obtained using this entrapment method, for which an average value of 64 ± 2.6% was measured. These results compare well with previous work showing 50–60% capture efficiency for BSA and up to 80% in one study 6, 7. The activity of the enzyme‐containing beads compared to the free enzyme activity (i.e., the activity of the enzyme added to the solution before bead formation) was also measured.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Good capture efficiencies were obtained using this entrapment method, for which an average value of 64 ± 2.6% was measured. These results compare well with previous work showing 50–60% capture efficiency for BSA and up to 80% in one study 6, 7. The activity of the enzyme‐containing beads compared to the free enzyme activity (i.e., the activity of the enzyme added to the solution before bead formation) was also measured.…”
Section: Resultssupporting
confidence: 90%
“…A shift in optimal operating conditions is often observed for immobilized enzymes and can be an advantage in the final application. Additionally, it has been observed that the pH of surrounding media has an effect on the rate of release of molecules entrapped in a chitosan gel matrix 7, 18. This may be attributable to the swelling characteristics of the chitosan gel, and could be used for pH‐triggered drug delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, "chitosan" refers to such deacetylated structures with varying molecular weights, degrees of deacetylation, and differential distribution of these deacetylated residues in the polymer network. Three-dimensional scaffolds of chitosan, in addition to chitosan films and membranes, have been fabricated by employing rapid prototyping (RP) technology [289]. Prototype modeling and visualization based on computeraided design and computer-aided manufacturing (CAD and CAM) have been instrumental in applications of the RP technology in tissue engineering [290].…”
Section: Smart Hydrogels In Flow Control and Biofabrication: Microflumentioning
confidence: 99%
“…Chitosan is an abundant, natural polymer with promising applications in the immobilization and controlled release of biological compounds. Various enzymes have been immobilized with chitosan using absorption,1, 2 covalent binding,3–9 or matrix entrapment 10–14. A primary benefit of matrix entrapment is that is can be used to immobilize enzymes and other proteins in a chitosan gel under mild processing conditions.…”
Section: Introductionmentioning
confidence: 99%